Neural Markers Associated with the Temporal Deployment of Attention: A Systematic Review of Non-motor Psychophysical Measures Post-stroke - Low, Essie; Laycock, Robin; Crewther, Sheila (Frontiers in Human Neuroscience, 2017)
In recent years, evidence has emerged to suggest abnormal temporal dynamics of attentional processing in stroke patients, especially those presenting with neglect symptoms. However, there has been little profiling of the nature and extent of such temporal anomalies. In addition, many paradigms currently used to measure the time required to deploy visual attention in stroke require a psychomotor response, and may therefore confound performance outcomes. Thus, the aim of this systematic review was to identify and evaluate studies that have employed non-motor psychophysical paradigms to characterize the temporal deployment of visual attention in space. A total of thirteen non-motor psychophysical studies were identified, in which stimulus exposure times were manipulated to measure the time course of attentional deployment. Findings suggest that prolonged attentional deployment thresholds are more likely to occur with lesions within more ventral areas of the fronto-parietal network, irrespective of whether patients presented with neglect. Furthermore, this deficit was greater following right-hemispheric lesions, suggesting a dominant role for the right-hemisphere in facilitating efficient deployment of attention. These findings indicate that area and hemisphere of lesion may serve as putative markers of attentional deployment efficiency. In addition, findings also provide support for using non-motor psychophysical paradigms as a more rigorous approach to measuring and understanding the temporal dynamics of attention.